Long-term exposure to PM1 and thyroid diseases in China - Jing Wang; Di Teng; Kaijie Yang; Siying Liu; Cihang Lu; Zhongyan Shan; Weiping Teng; Yongze Li (European Thyroid Journal)
Background: Globally prevalent, thyroid diseases are linked to environmental factors such as air pollution. This study examines the link between particulate matter (PM)1 exposure and thyroid disease rates in China. Methods: We analyzed data from 73,900 adults across 31 Chinese provinces, using a high-resolution spatial–temporal extremity tree model to estimate PM1 and PM2.5 levels, and thyroid function tests to assess disease prevalence. Multivariate-adjusted ORs evaluated PM1’s link to thyroid disease. This cross-sectional study is adept at identifying associations but cannot establish causality due to its single-time data collection limitation. Results: Higher PM1 level exposure was significantly linked to an increased prevalence of thyroid diseases, including overt hypothyroidism, autoimmune thyroiditis (AIT), and TgAb positivity. A linear dose–response relationship was observed between PM1 concentration and both AIT and TgAb positivity. The study also revealed a significant association between PM1 exposure and autoimmune overt hypothyroidism, suggesting that thyroid dysfunction may be primarily mediated through autoimmune mechanisms. In addition, iodine status significantly influenced PM1’s effects, with lower levels enhancing susceptibility to thyroid issues. Furthermore, every 1% increase in the PM1/PM2.5 ratio was related to the prevalence of overt hypothyroidism (OR = 1.03; 95% CI: 1.03–1.04) and subclinical hypothyroidism (OR = 1.03; 95% CI: 1.03–1.04). Conclusions: PM1 exposure is associated with thyroid diseases, particularly AIT and TgAb positivity, with iodine status playing a modifying role. PM1 may be a key factor in PM2.5-related thyroid disease risk. Further prospective cohort studies are warranted to validate these findings.